Antidiabetic activity of aqueous extract of Sigesbeckia orientalis (St. Paul’s Wort) in alloxan-induced diabetes model (Brazilian Journal of Pharmaceutical Sciences, 2019)
The current study evaluated antidiabetic and antihyperlipidemic activities of aqueous extract of Sigesbeckia orientalis L. (St. Paul’s Wort) (AESO) in an alloxan-induced diabetic rat model. Following OECD guidelines safe doses of AESO were assessed in rats for the main study. Serum/bood glucose, α-amylase, and lipids levels and histopathological evaluations were conducted to assess antidiabetic and associated antihyperlipidemic efficacies of AESO. AESO was found to be safe up to the dose of 2000 mg/kg. Significant (p < 0.05) reduction in glucose and lipids (total cholesterol, triglycerides, low‑density lipoproteins) levels was observed in AESO treatment groups. Serum α-amylase, high‑density lipoproteins, and total body weight was increased significantly (p < 0.05) in diabetic rats treated with AESO. Histopathological data showed improvement in hepatocyte and pancreatic β-cells islets architecture. HPLC analysis identified quercetin, gallic acid, vanillic acid, p-coumaric acid, m-coumaric acid and cinnamic acid in AESO which are suggested to be responsible for observed antihyperglycemic and antihyperlipidemic attributes. Further studies to standardise the extract and evaluation of safety profile in long-term toxicity studies are recommended for safe and effective antidiabetic nutraceuticals development.